Forms of government and municipal financial performance. Issue 4 (19th May 2023) - Lee, Hakyeon; Park, Jinsol; Butler, J. S.
IMPACT: This paper finds that the political influence of a local mayor on the appointment of the chief administrative officer (CAO) has a negative influence on the financial outcomes of local governments, as evidenced by lower municipal bond ratings. This finding suggests that excessive political authority delegated to mayors may restrict managers from using long-term and apolitical financial strategies. The authors urge local governments to have a mechanism that insulates their CAOs from political pressures to increase government efficiency and decrease the risk of corruption.